Congenital Descending Aorta-Right Atrial Tunnel: A Case Report - Zhang, Xing; Su, Zhongjian; Yang, Yanfei; Ge, Liping; Li, Bin (Frontiers in Pediatrics, 2020)
Introduction: Congenital descending aorta-right atrial tunnel is a rare congenital heart defect. Herein, a new case successfully treated by transcatheter closure using a new type of ventricular septal defect occluder from the aortic side was reported. Case Presentation: An 11-month-old Chinese girl presenting with a cardiac murmur was suspected with partial anomalous pulmonary venous connection as assessed by echocardiography. Descending aorta-right atrial tunnel was confirmed by computed tomography angiography and cardiac catheterization. Subsequently, transcatheter closure was performed successfully using a new type of ventricular septal defect occluder from the aortic side. The cardiac murmur disappeared after the intervention, and echocardiography did not reveal any abnormal flow inside the right atrium. At 6 months, the patient had no murmur, and no residual shunt was found using the echocardiogram. Conclusion: Descending aorta-right atrial tunnel is a rare anomaly. Transcatheter closure was successful in our case. Long-term follow-up is needed to assess any progressive growth of the residual tunnel.